A noisy sub-Imperialist: Richard Seddon and the attempt to establish a New Zealand empire in the Pacific, 1894–1901. Issue 2 (1st October 2014) - Brooking, Tom
This article will be divided into four parts. First, it will traverse the surprisingly rich historiography on Richard Seddon's efforts to establish a New Zealand sub-Empire in the Pacific. Most commentary has been relatively benign, especially that resulting from the many theses written in my own department, at the University of Otago, under Angus Ross in the 1960s. In the 1980s these adventures began to be viewed more critically by the likes of Dick Scott and Malama Meleisea. General histories of the Pacific, though, such as those written by Kerry Howe and Ian Campbell, have tended to ignore Seddon and other leading New Zealand politicians who dreamed of a sub-Empire in the Pacific, such as George Grey, Robert Stout and John Ballance. More recently, Damon Salesa, as one of the first indigenous historians of the Pacific, has judged Seddon's efforts in particular, and New Zealand's record in general, rather more harshly. So too, have scholars in anthropology, especially those influenced by postcolonial theory.Second, I will tell the story of how New Zealand only managed to gain control of the Cook Islands and Niue, even though Seddon hoped to govern Western Samoa and Fiji, and, potentially, Tonga, the New Hebrides and Hawai'i. Third, I will explain how utilizing the insights of the decidedly middle-aged 'new' Imperial history might provide a better sense of context, especially in terms of Seddon's efforts at trying to build a 'better Britain' while expanding the 'British world'. Fourth, the problem remains that the success or failure of the New Zealand effort requires some comparative or transnational analysis to discover if the most remote British colony fared better or worse than other major Empires in the Pacific. The most obvious comparison is with the other sub-Imperial power – Australia – and I will suggest some ways in which such a comparison might be made, as well as discuss Seddon's views of the efforts of his trans-Tasman neighbour in comparison with his own.